PENGGUNAAN TEKNOLOGI INFORMASI DALAM PELAYANAN SIRKULASI DI PERPUSTAKAAN - Eviendrita Eviendrita (UIN Imam Bonjol Padang, 2019)
Libraries are services, so there is no library without services.The service here means the user of library services. This kind of work activity is often referred to as